Effect of a Hemodialysis Session on Markers of Inflammation and Endotoxin - Shyam Dheda; David A Vesey; Carmel Hawley; David W Johnson; Magid Fahim (Hindawi Limited, 2022)
Background. People receiving hemodialysis (HD) treatment have higher cardiovascular morbidity and mortality, ascribed to an increased prevalence of traditional cardiovascular risk factors. However, the role of nontraditional risk factors, such as inflammation, has become increasingly recognized. The origin of this inflammation remains elusive and one putative cause is elevated levels of circulating bacterial endotoxin. Methods. In this study, serum concentrations of endotoxin and inflammatory biomarkers, including high-sensitivity C-reactive protein (hsCRP), interleukin-6 (IL-6), interleukin-1β (IL1β), ferritin and tumor necrosis factor (TNF), were measured in 30 adults receiving HD and 10 healthy individuals without kidney disease. In people receiving HD, samples were collected immediately before dialysis (preHD), after dialysis (postHD), and 48 hours after (postHD48hrs). Results. Endotoxin was detectable in only 1 of 90 samples analyzed. There were no significant differences in serum hsCRP, IL1β, and IL6 levels, before and after dialysis. Serum TNF levels decreased significantly from 30.9 (8.0, 39.5) pg/mL preHD to 13.9 (8.5, 17.3) pg/mL post-HD (p=0.002) and then increased back to 27.37 (14.5, 35) pg/mL 2 days later (p<0.001). Ferritin increased from 1153 ng/mL (782, 1458) preHD to 1313 ng/mL (657, 1638) post HD (p<0.001) and then decreased back to 1186 ng/mL (754, 1597) (p=0.66) postHD48hrs. Compared to controls, people receiving HD had significantly elevated levels of hsCRP [6.16 mg/L (2.1, 16.8) vs. 1.1 mg/L (0.81, 3.63) p=0.015], IL1β [1.5 pg/mL (0.05, 2.51) vs. 0.5 pg/mL (1.81, 2.95) p≤0.001], and ferritin [1153 (782, 1458) vs. 132.9 (111, 257) ng/mL p≤0.001], but comparable levels of in IL6 [6.15 pg/mL (4.82, 9.12) vs. 7.49 pg/mL (4.56, 10.39), p=0.77] and TNF [27.35 pg/mL ± 17.48 vs. 17.87 pg/mL ± 12.28, p<0.12]. In conclusion, people on HD have elevated levels of inflammatory biomarkers, which are not associated with endotoxemia (which is rare) or the dialysis procedure.